Synthesis of Pyrazolone Derivatives and Their Nanometer Ag(I) Complexes and Physicochemical, DNA Binding, Antitumor, and Theoretical Implementations - Ismail Althagafi; Nashwa M. El-Metwaly; Marwa G. Elghalban; Thoraya A. Farghaly; Abdalla M. Khedr (Bioinorganic Chemistry and Applications)
Four pyrazolone derivatives and their corresponding silver complexes were synthesized and characterized. Based on elemental analysis, 1 : 2 (M : L) molar ratio was suggested for all inspected complexes. 1H, 13C NMR, mass, UV-Vis, TGA, and IR were the spectral tools used for describing the formulae. Moreover, XRD patterns and SEM pictures were used to evaluate the particle sizes which appeared strongly in nanometer range. CT-DNA study is the major consideration in this study, to test the interacting ability of all synthesized cationic complexes towards cell DNA. Each binding constant was computed and correlated with the Hammett sigma constant. Antitumor activity was examined upon three carcinoma cell lines (MCF-7, HepG2, and HCT116). The high efficiency was recorded towards MCF-7 (breast carcinoma) cell line. Kinetic studies yield essential parameters to assert on the rule of metal atom on thermal feature of organic compounds. Molecular modeling was implemented to optimize the structures of compounds. Also, molecular docking was achieved to obtain a clear view about proposed drug behavior within the affected cells. This was achieved through comparing the calculated internal energy values of all docking complexes. All the tested compounds displayed a significant interaction with breast cancer protein (strong matching with practical result) followed by DNA polymerase protein.